Prevention Of Thromboembolic Complications In Postoperative Bemoans - X.A.Abdullayev; Muratov TM.N (Genius Journals, 2024)
Pulmonary artery thromboembolism is one of the most common emergencies in the postoperative period. Pulmonary artery thromboembolism is a pathological condition caused by thromboembolism of the trunk or small branches of arteries in the small circulatory circle, initially, the right ventricle later leading to the development of biventricular heart failure. Pulmonary embolism is the third most common in mortality from cardiovascular disease after myocardial infarction and stroke. In economically developed countries, 0.1% of the population dies from this pathology every year.It is impossible to accurately assess the frequency of oate after surgery, since this condition is often asymptomatic.
Keywords: alanine-amino-transferase; aspartate-amino-transferase; deposition rate